Ultrahigh molecular weight polyethylene/graphene oxide nanocomposites: Wear characterization and biological response to wear particles. Issue 1 (9th December 2016) - Suñer, S.; Gowland, N.; Craven, R.; Joffe, R.; Emami, N.; Tipper, J. L.
Abstract: In the field of total joint replacements, polymer nanocomposites are being investigated as alternatives to ultrahigh molecular weight polyethylene (UHMWPE) for acetabular cup bearings. The objective of this study was to investigate the wear performance and biocompatibility of UHMWPE/graphene oxide (GO) nanocomposites. This study revealed that low concentrations of GO nanoparticles (0.5 wt %) do not significantly alter the wear performance of UHMWPE. In contrast, the addition of higher concentrations (2 wt %) led to a significant reduction in wear. In terms of biocompatibility, UHMWPE/GO wear particles did not show any adverse effects on L929 fibroblast and PBMNC viability at any of the concentrations tested over time. Moreover, the addition of GO to a UHMWPE matrix did not significantly affect the inflammatory response to wear particles. Further work is required to optimize the manufacturing processes to improve the mechanical properties of the nanocomposites and additional biocompatibility testing should be performed to understand the potential clinical application of these materials. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 183–190, 2018.